2023
DOI: 10.3390/cells12081163
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms of Aging and Aging-Associated Diseases

Abstract: Aging is an inevitable outcome of life, characterized by a progressive decline in tissue and organ function. At a molecular level, it is marked by the gradual alterations of biomolecules. Indeed, important changes are observed on the DNA, as well as at a protein level, that are influenced by both genetic and environmental parameters. These molecular changes directly contribute to the development or progression of several human pathologies, including cancer, diabetes, osteoporosis, neurodegenerative disorders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 224 publications
0
5
0
Order By: Relevance
“…Over the last decade, a large number of studies have shown that epigenetic changes are one of the major causes of cellular senescence, affecting gene expression, but not disrupting DNA sequences. Epigenetic mechanisms include DNA methylation, histone modification, and changes in non-coding RNA expression [ 114 ].…”
Section: Inducers and Key Signatures Of Cellular Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, a large number of studies have shown that epigenetic changes are one of the major causes of cellular senescence, affecting gene expression, but not disrupting DNA sequences. Epigenetic mechanisms include DNA methylation, histone modification, and changes in non-coding RNA expression [ 114 ].…”
Section: Inducers and Key Signatures Of Cellular Senescencementioning
confidence: 99%
“…Over the last decade, a large number of studies have shown that epigenetic changes are one of the major causes of cellular senescence, affecting gene expression, but not disrupting DNA sequences. Epigenetic mechanisms include DNA methylation, histone modification, and changes in non-coding RNA expression [114]. In a study by Giuliani et al [110], mitomiR-34a, -146, and -181a are overexpressed in replicatively senescent HUVECs, suppressing the activity of the apoptotic protein Bcl-2, which is responsible for the inhibition of apoptosis and autophagy.…”
Section: Epigenetic Changesmentioning
confidence: 99%
“…AA. Epigenetic modifications of the genome via direct methylation or indirectly via modification of histones, as well as modification of RNA can occur under a variety of circumstances (discussed in [78][79][80][81][82]). Many of these alterations are reversible modifications that allow for modulation and regulation of gene expression and function.…”
Section: Summary Of Points Potentially Relevant To Post-menopausal Co...mentioning
confidence: 99%
“…By 2030 and 2050 the proportion of this age group is projected to be 12% and 16%, respectively 2 . Several molecular mechanisms that regulate aging have been discovered, such as telomere dysfunction 3 , loss of proteostasis 4 , mitochondrial dysfunction 5 , stem cell exhaustion 6 , and epigenetic alterations 7 . The aging process is driven by several complex and important pathways, many of which are associated with chronic oxidative stress (OS) caused by elevated levels of reactive oxygen species (ROS) 8 .…”
Section: Introductionmentioning
confidence: 99%